The Flavonoid Hesperetin Alleviates Behavioral Abnormality in 6-Hydroxydopamine Rat Model of Hemi-Parkinsonism - Tourandokht Baluchnejadmojarad; Mehrdad Roghani (Basic and Clinical Neuroscience, 2010)
ABSTRACTParkinson’s disease (PD) is a neuropathological and debilitating disorder involving the degeneration of mesencephalic dopaminergic neurons. Neuroprotective effect of hesperetin has already been reported, therefore, this study examined whether the administration of this flavonoid would attenuate behavioral abnormalities in an experimental model of PD in rat. For this purpose, unilateral intrastriatal 6-hydroxydopamine (6-OHDA, 12.5 μg/5μl of saline-ascorbate)-lesioned rats were pretreated i.p. with hesperetin (10 mg/kg). It was found out that hesperetin administration attenuates the rotational behavior in lesioned rats. In summary, hesperetin administration attenuates behavioral abnormality in hemiparkinsonian rats and this may be of benefit, along with other therapies, in neurodegenerative disorders including PD.